P2 4 Barry Steakfries and the Jetpack Joyride - Brough, Oliver J. T.; Gardiner, Corban C. B.; Grout, Joel E.; Halliday, Tom E. (Physics Special Topics, 2023)
We investigate the feasibility of using a twin machine gun jetpack for controlled flight as seen in the mobile game Jetpack Joyride. Utilizing two lightweight M134s, weighing 19 kg each, we found that this jetpack would support the weight of the average adult male and a stabilising counterweight, but would only have a flight time of 15 seconds.